Directivos y comunidades de aprendizaje docente: un campo en construcción (Directors and teacher learning communities: a field under construction) - Vaillant, Denise (Revista Eletrônica de Educação, 2019)
The community and collaborative dimension of the teaching activity does not seem to be reflected in the decision-making of most of the educational centers. It follows the managerial challenge of setting up spaces that favor learning and teamwork among teachers. The author explains the benefits of having a community of practice or professional learning community, institutions to which she attributes an enormous potential to exchange, collaborate and innovate pedagogically. This forces us to rethink the traditional format of the educational center, betting on a professional development that generates new ways of learning among teachers in favor of the learning of students. Resumo A dimensão comunitária e colaborativa da atividade docente parece não se refletir na tomada de decisão da maioria dos centros educacionais. Segue o desafio gerencial de montar espaços que favoreçam a aprendizagem e o trabalho em equipe entre os professores. O autor explica os benefícios de se ter uma comunidade de prática ou comunidade de aprendizagem profissional, entidades para as quais ela atribui um enorme potencial para trocar, colaborar e inovar pedagogicamente. Isso nos obriga a repensar o formato tradicional do centro educacional, apostando em um desenvolvimento profissional que gera novas formas de aprendizagem entre os professores em favor do aprendizado dos alunos. Resumen La dimensión comunitaria y colaborativa de la actividad docente parece no reflejarse en la toma de decisiones de la mayoría de los centros educativos. De ello se desprende el desafío directivo de poner en marcha espacios que favorezcan el aprendizaje y trabajo en equipo entre docentes. La autora explicita los beneficios de contar con una comunidad de práctica o comunidad profesional de aprendizaje, entidades a las que atribuye un enorme potencial para intercambiar, colaborar e innovar pedagógicamente. Esto obliga a repensar el formato tradicional de centro educativo, apostando a un desarrollo profesional que genere nuevas formas de aprender entre los profesores en pos del aprendizaje de los estudiantes. Keywords: Professional learning community, Directors, Teachers, Student learning. Palavras-chave: Comunidade de aprendizagem profissional, Diretores, Professores, Aprendizado dos alunos. Palabras claves: Comunidad de aprendizaje profesional, Directores, Profesores, Aprendizaje de los alumnos. References ANDERSON, S. Liderazgo Directivo: Claves para una Mejor Escuela. Psicoperspectivas, Vol.9, n.2, 2010, pp.34-52. Recuperado de: http://www.psicoperspectivas.cl/index.php/psicoperspectivas/article/view/127/141 AGUERRONDO, I.; VAILLANT, D. El aprendizaje bajo la lupa: Nuevas perspectivas para América Latina y el Caribe. UNICEF: Panamá, 2015. BOLÍVAR, A.; LÓPEZ, J.; MURILLO, F.J. Liderazgo en las instituciones educativas. Una revisión de líneas de investigación. Revista Fuentes, 14, 2013, pp.15-60. BOYLE, B.; WHILE, D.; BOYLE, T. A longitudinal study of teacher change: What makes professional development effective? The Curriculum Journal, 15(1), 2004, pp. 45-68. CALVO, G. Desarrollo Profesional Docente: el aprendizaje profesional colaborativo. In: UNESCO-OREALC. Temas críticos para formular nuevas políticas docentes en América Latina y el Caribe: el debate actual. Santiago de Chile: CEPPE y UNESCO, 2014. CUENCA; R.; PONT; B. El liderazgo escolar: factor clave para reforma educativa. Madrid: Fundación Santillana, 2016. COWAN, J. E. Strategies for Developing a Community of Practice: Nine Years of Lessons Learned in a Hybrid Technology Education Master’s Program. Tech Trends: Linking Research at Practice to Improve Learning, 56(1), 2012, pp.12-18. DARLING-HAMMOND, L.; CHUNG WEI, R.; ANDREE, A.; RICHARDSON, N.; ORPHANOS, S. Professional Learning in the Learning Profession: A Status Report on Teacher Development in the United States and Abroad. USA: National Staff Development Council, 2009. DAY, C.; SAMMONS, P. Successful leadership: a review of the international literature. United Kingdom: The University of Nottingham, 2013. DUFOUR, R. What is a “professional learning community”? Educational Leadership, 61(8), 2004, pp.6-11. DUFOUR, R. Work together: But only if you want to. Phi Delta Kappan, XCII (5), 2011, pp. 57-61. GAIRÍN SALLÁN, J. Las comunidades de práctica profesional. Creación, desarrollo y evaluación. Madrid: Wolters Kluwer, 2015. GORDON, S. P. Professional Development for School Improvement: Empowering Learning Communities. Boston, M A: Allyn and Bacon, 2006. HARGREAVES, A.; FULLAN, M. Professional Capital. Teachers College, Columbia University, 2012. HAUSMAN, C. S.; GOLDRING, E. B. Sustaining teacher commitment: The role of professional communities. Peabody Journal of Education, 76(2), 2001, pp. 30-51. HORD, S. M.; SOMMERS, W. A. Leading Professional Learning Communities: Voices from Research and Practice. Londres: Sage, 2008. KANOLD, T. The Five Disciplines of PLC Leaders. Bloomington, IN: Solution Tree Press, 2011. KORTHAGEN, F.; LOUGHRAN, J.; RUSSELL, T. Developing fundamental principles for teacher education programs and practices. Teaching and Teacher Education, 22(8), 2006, pp. 1020–1041. LECLERC, M. Communauté d’apprentissage professionnelle: guide à l’intention des leaders scolaires. Québec: Presses de l’Université du Québec, 2012. LEITHWOOD, K. Transformational school leadership for large-scale reform: Effects on students, teachers, and their classroom practices. School Effectiveness and School Improvement, 2006, pp. 202-227. LEITHWOOD, K.; LOUIS, K. S. Linking Leadership to Student Learning. San Francisco: Jossey-Bass, 2011. MARCELO GARCÍA, C.; VAILLANT, D. Desarrollo Profesional Docente. ¿Cómo se aprende a enseñar? Madrid: Narcea, 2009. MONTECINOS, C. Desarrollo Profesional Docente y Aprendizaje Colectivo. Psicoperspectivas [en línea] II (Sin mes), 2003. MURILLO, J.; ROMÁN, M. La distribución del tiempo de los directores y las directoras de escuelas de Educación Primaria en América Latina y su incidencia en el desempeño de los estudiantes. Revista de Educación, 361, 2013, mayo-agosto, pp. 1-21. OECD. PISA 2015 Results (Volume II): Policies and Practices for Successful Schools, PISA, OECD Publishing, Paris, 2016. http://dx.doi.org/10.1787/9789264267510-en OECD Leadership for 21st Century Learning, Educational Research and Innovation, OECD Publishing, 2013. PONT, B.; NUSCHE, D.; MOORMAN, H. Improving School Leadership. Volume 1: Policy and Practice. Paris: OECD, 2008. REIMER, T. L. A Study on the Principal’s Role in the Development of Professional Learning Communities in Elementary Schools that «Beat the Odds » in Reading. Minnesota: University of Minnesota, 2010. ROY, P.; HORD, S. M. It’s everywhere, but what is it? Professional learning communities. Journal of School Leadership, 16, 2006, pp. 490-501. SCHÖN, D. A. How Professionals Think in Action. New York, NJ: Basic Books, 1983. SPILLANE, J. P. The Practice of Leading and managing Teaching in Educational Organisations. OCDE (2013), Leadership for XXIst Century Learning, OCDE Publishing, 2013. STOLL, L.; SEASHORE LOUIS, K. Professional Learning Communities: Divergence, Depth and Dilemmas. New York: McGraw Hill, 2007. STOLL, L.; BOLAM, R.; MCMAHON, A.; WALLACE, M.; THOMAS, S. Professional learning communities: A review of the literature. Journal of Educational Change, 7(4), 2006, pp. 221-258. UNESCO-IIPE-IWGE. From schooling to learning. Paris: UNESCO/International Institute for Educational Planning. 2012.http://unesdoc.unesco.org/images/0021/002192/219289e.pdf UNESCO-OREALC Temas críticos para formular nuevas políticas docentes en América Latina y el Caribe: el debate actual. Santiago de Chile: CEPPE y UNESCO, 2013. UNESCO-OREALC Antecedentes y Criterios para la Elaboración de Políticas Docentes en América Latina y el Caribe. Santiago de Chile: CEPPE y UNESCO, 2014. VAILLANT, D. Trabajo colaborativo y nuevos escenarios para el desarrollo profesional docente. In: Revista Docencia Año XX Número 60, Santiago de Chile: Colegio de Profesores de Chile, 2016. VAILLANT, D. Liderazgo escolar, evolución de políticas y prácticas y mejora de la calidad educativa. Documento ED/EFA/MRT/2015/PI/9. Paris: UNESCO, 2015. Recuperado de: http://unesdoc.unesco.org/images/0023/002324/232403s.pdf VAILLANT, D. Formación inicial del profesorado en América Latina: dilemas centrales y perspectivas. Revista Española de Educación Comparada, Madrid, v. 22, 2013, pp. 185-206. Recuperado de: http://denisevaillant.com/articulos/2013/Formacion_inicial_profesorado_America_Latina.pdf VAILLANT, D.; MARCELO GARCÍA, C. El A, B, C, D de la Formación Docente. Narcea: Madrid, 2015. WEINSTEIN, J. Liderazgo directivo, asignatura pendiente de la reforma educacional chilena. Revista de Estudios Sociales, 117, 2009, pp. 123-148. WEINSTEIN; MUÑOZ; HERNÁNDEZ. El liderazgo escolar en América Latina y el Caribe. Un estado del arte en base a ocho sistemas escolares de la región. Santiago de Chile: OREALC/UNESCO, 2014. WENGER, E. Communities of Practice: Learning, Meaning and Identity. Cambridge: Cambridge University Press, 1998. ZEPEDA, S. Professional Development. What Works. Larchmont, NY: Eye on Education, 2012.